Novel Molecular Subtypes and Related Score Based on Histone Acetylation Modification in Renal Clear Cell Carcinoma - Wang, Shichao; Xiang, Ting; Yu, Ling; Wen, Junmao; Liu, Fang; Yang, Dong; Wu, Wei; Hu, Ling (Frontiers in Cell and Developmental Biology, 2021)
Background: histone acetylation modification has been found to be correlated the development of renal carcinoma, however, its role in clear cell renal carcinoma (ccRCC) remains to investigate. Thus, this study aimed at identifying the molecular subtypes and establish a relevant score based on histone acetylation modification in ccRCC. Methods: Gene expression and mutation data were retrieved from The Cancer Genome Atlas database. Molecular subtypes were identified by unsupervised clustering based on the histone acetylation regulators expression, and the molecular and clinical characteristics including survival, tumor microenvironment, gene set variation, immune cells infiltration, and immune checkpoints in each subtype were investigated. Next, we employed univariate Cox analysis to analyze these genes and established acetylation-related score by lasso regression analysis. Furthermore, we investigated the differences including survival, signaling pathways, mutational landscape, tumor mutation burden (TMB) between high-risk and low-risk groups. The established score was validated by receiver operative curve, univariate and multivariate Cox regression analyses. We also established a nomogram including acetylation score, age, gender, grade, and stage and verified it by decision curve analysis and calibration plot. The E-MTAB-1980 cohort from ArrayExpress database was employed as a reference to validate the established score. Results: Thirty-three types of histone acetylation regulators were employed in this study, and two clusters were identified. The two clusters presented significant differences in survival, tumor microenvironment, immune cells infiltration, immune checkpoints, and signaling pathways. Furthermore, an acetylation-related score, composed of six genes (BRD9, HDAC10, KAT2A, KAT5, BRDT, SIRT1, KAT6A, HDAC5), was verified to be significantly associated with prognosis and TMB. Thus, the established scores were successfully verified by the validated cohort. And the nomogram was constructed and successfully validated. Conclusion: The identification of the histone acetylation-related subtypes and score in our study may help reveal the potential relation between histone acetylation and immunity and provide novel insights for the development of individualized therapy for ccRCC.